Can international experience of returnee senior managers contribute to the improvement of CSR performance- Evidence from China - Qian, Junhui (2019)
As the competition among countries becomes more and more intense, returnee talents with international experience play a significant role in promoting economic performance as the scarce resource, not only from the organisational level but also from the individual level, especially in developing countries. Meanwhile, the public attention has been attracted by corporate social responsibility (CSR) since the 1990s with the development of the economy.